The Prognostic Significance of the CALLY Index in Ampullary Carcinoma: An Inflammation-Nutrition Retrospective Analysis - Xi P; Huang G; Huang K; Qin D; Yao Z; Jiang L; Zhu Q; He C (Journal of Inflammation Research)
Pu Xi,1,* Guizhong Huang,1,* Kewei Huang,2,* Dailei Qin,1 Zehui Yao,1 Lingmin Jiang,1 Qi Zhu,1 Chaobin He1 1Department of Pancreatobiliary Surgery, State Key Laboratory of Oncology in South China, Guangdong Provincial Clinical Research Center for Cancer, Sun Yat-Sen University Cancer Center, Guangzhou, 510060, People’s Republic of China; 2State Key Laboratory of Oncology in South China, Department of Clinical Laboratory, Collaborative Innovation Center for Cancer Medicine, Sun Yat-Sen University Cancer Center, Guangzhou, 510060, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chaobin He, Department of Pancreatobiliary Surgery, State Key Laboratory of Oncology in South China, Guangdong Provincial Clinical Research Center for Cancer, Sun Yat-sen University Cancer Center, 651 Dongfeng Road E, Guangzhou, Guangdong, 510060, People’s Republic of China, Email hechb@sysucc.org.cnBackground: As a novel inflammatory-nutritional biomarker, the C-reactive protein–albumin–lymphocyte (CALLY) index has demonstrated significant prognostic value in various malignancies. However, research on its association with the prognosis of ampullary carcinoma (AC) is rare. This study aims to investigate the relationship between the CALLY index and the prognosis of patients with AC.Methods: We retrospectively analyzed data from 201 patients with AC at Sun Yat-sen University Cancer Center. Several clinicopathological factors and biomarkers were included in the study. Univariate and multivariate Cox regression analyses, along with competing risk analysis, were performed to identify prognostic factors for AC after pancreaticoduodenectomy (PD). Only factors with significant results in univariate analysis were included in multivariate analysis. To ensure the robustness of our findings, propensity score matching (PSM) analyses were conducted to assess survival differences according to the CALLY index.Results: The univariate and multivariate Cox regression analyses revealed that pathological type, N stage, T stage, postoperative chemotherapy regimen, and the CALLY index were all statistically significant prognostic factors for patients with AC after PD (all P values < 0.05). Taking into account non-cancer-related mortality as competing hazards, these factors remained significant predictors (all P values < 0.05). After PSM, the survival advantage observed between the low and high CALLY groups remained discernible and consistent.Conclusion: This study indicated that a reduced CALLY index correlates with a poorer cancer-specific survival in AC patients after PD, highlighting its utility as a prognostic marker for this condition.Keywords: ampullary carcinoma, prognosis, inflammation-nutritional-index, competing risk analysis, propensity matching analysis